Ijtihad Progresif Ibn Hazm (994-1064 M) dalam Merespon Perubahan Sosial - Syufa'at, Syufa'at (Fakultas Syariah IAIN Purwokerto, 2011)
Now the issue of ijtihad proposed as one of the key themes of reform efforts and refreshment understanding of religion. Ibn Hazm perform ijtihad in certain respects a more contextual approach, rather than textual. This means, he was prosecuted for not only active and proactive, but at the same time progressive. Methodology renewal of Islamic religious thought, according to Ibn Hazm always connects normativitas tradeoffs between the dimensions of the verses of the Qur'an and Sunnah as the dimensions of the historicity of understanding these verses at the level of socio-historical life of the local muslim community.